2011
DOI: 10.1080/12538078.2011.10516292
|View full text |Cite
|
Sign up to set email alerts
|

Activité antioxydante et composition chimique des huiles essentielles de quatre espèces de thym du Maroc

Abstract: Mots clés : huile essentielle -Thymus capitatus -Thymus ciliatus -Thymus bleicherianus -Thymus algeriensis -composition chimique -activité antioxydante.Abstract.-The chemical composition of four Thymus species essential oils (T. capitatus, T. ciliatus, T. bleicherianus and T. algeriensis) was determined by GCand GC/SM. The essential oil of T. capitatus is dominated by carvacrol (70.92%), that of T. ciliatus by thymol (44.2%), that of T. bleicherianus contains α-terpinene (42.23%) and thymol (23.95%) as major c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 43 publications
2
22
0
Order By: Relevance
“…This chemotype has never been reported for T. munbyanus before. In fact, previous studies conducted on plant samples collected in different areas of Algeria reported carvacrol (71.4 – 80.3%), carvacrol (35.2%) and thymol (18.5%), thymol (44.2%), thymol (37.7%) and p ‐cymene (14.7%), thymol (52.0 – 60.5%) and γ ‐terpinene (9.5 – 11.3%), thymol (44.2%), ( E )‐ β ‐ocimene (25.8%) and α ‐terpinene (12.3%), camphor (21.8 – 24.9%), camphene (13.5 – 17.3%) and 1,8‐cineole (11.9 – 15.7%), as the major essential oil constituents. Only in a few studies, the subspecies investigated (subsp.…”
Section: Resultsmentioning
confidence: 95%
See 2 more Smart Citations
“…This chemotype has never been reported for T. munbyanus before. In fact, previous studies conducted on plant samples collected in different areas of Algeria reported carvacrol (71.4 – 80.3%), carvacrol (35.2%) and thymol (18.5%), thymol (44.2%), thymol (37.7%) and p ‐cymene (14.7%), thymol (52.0 – 60.5%) and γ ‐terpinene (9.5 – 11.3%), thymol (44.2%), ( E )‐ β ‐ocimene (25.8%) and α ‐terpinene (12.3%), camphor (21.8 – 24.9%), camphene (13.5 – 17.3%) and 1,8‐cineole (11.9 – 15.7%), as the major essential oil constituents. Only in a few studies, the subspecies investigated (subsp.…”
Section: Resultsmentioning
confidence: 95%
“…However, in most cases only the subsp. ciliatus was analysed, while for the rest of the studies the subspecific level was not determined . In the above studies the most abundant volatile components reported were the phenols thymol and carvacrol, and their precursors p ‐cymene and γ ‐terpinene.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The strong antibacterial activity of the pure essential oil of Thymbra capitata is rather due to its chemical profile rich in carvacrol (85.35%) which is known for its antibacterial power [55]. [56]. Similarly, the essential oil of Thymus vulgaris, comprises almost the same chemical composition as the studied Thymbra capitata [carvacrol (83.8%), terpinene (4.96%) and pcymene (8.15%)], showed great antibacterial effect [57].…”
Section: Comparison Of the Chemical Composition Of Pure Essential Oilmentioning
confidence: 99%
“…However, when compared to the pure reference antioxidant BHT (0.11±0.002 mg/ml), all the tested EOs showed a significantly lower antioxidant activity (p<0.05). T. bleherianus EOs showed the lowest activity than that founded by Amarti et al (IC 50 = 77.8 μg/ml) [48], and also lowest than T. serpyllum, Thymus algeriensis, and Thymus vulgaris with IC 50 = 0.96 μg/ml, IC 50 = 1.64 μg/ml, and IC 50 = 4.80 μg/ml, respectively, reported by Nikolić et al [49].…”
Section: Dpph Radical Scavenging Activitymentioning
confidence: 63%